1988
DOI: 10.1029/wr024i002p00315
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “A natural gradient experiment on solute transport in a sandy aquifer: Spatial variability of hydraulic conductivity and its role in the dispersion process” by E. A. Sudicky

Abstract: Sudicky's [1986] article presents an analysis of the spatial variability of hydraulic conductivity at the Borden site. The results of this analysis are consequently used to calculate dispersion parameters, based on the three-dimensional transport theory developed by Gethar and Axness [1983] and the vertically averaged, two-dimensional approach developed by Dagan [1982Dagan [ , 1984. The Borden experiment is very unique and valuable to the groundwater community, and the contribution of the researchers involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…An approximate estimate of the time required to smooth the initial surface, denoted T•, can be obtained as follows. Solute "particles" as defined by Dagan [1984] [Kemblowski, 1988;Sudicky, 1988]. The averaging length suggested by Dagan [1987] is a single vertical correlation length of the log hydraulic conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…An approximate estimate of the time required to smooth the initial surface, denoted T•, can be obtained as follows. Solute "particles" as defined by Dagan [1984] [Kemblowski, 1988;Sudicky, 1988]. The averaging length suggested by Dagan [1987] is a single vertical correlation length of the log hydraulic conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…Given this sample volume and taking into account the porosity, the measured concentration is representative of an average within a sphere surrounding the point of extraction that is of the order of Sudicky's estimated vertical correlation of ln( K ) equal to 0.12. Following from Kemblowski [1988, equation (7)] or Dagan [1989a, equation (4.7.1)], the reduction of the variance of a vertically graded (averaged) process would consequently be a factor of 2 e −1 or 0.74. Sudicky [1988] uses this logic in arguing support for the use of a leading constant β = 0.74 in his model for plume spreading, as was suggested to him by Dagan.…”
Section: Metrics Characterizing the Plume Spreading Observed In The Bmentioning
confidence: 99%
“…The models of Dagan [1987] and Gelhar and Axness [1983] which Sudicky [1986] evaluated are based on the integral scale, traditionally determined by fitting model curves to sample bivariate statistics computed from large numbers of spatially distributed permeability data. Discussion of the spatial bivariate correlation of log conductivity and modeling it, including estimating its integral scale, can be found in work by Kemblowski [1988], Sudicky [1988], Woodbury and Sudicky [1991], Turcke and Kueper [1996], and Ritzi and Allen‐King [2007]. Modeling the spatial bivariate correlation is problematic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear variogram fitting procedure also revealed that considerable uncertainty can exist in the values of the geostatistical parameters, which, in turn, will lead to uncertainty in the values of effective, large‐scale transport parameters predicted by stochastic theory. Other discussions pertaining to the Borden tracer experiment and subsequent interpretations are given by Sudicky [1988a, 1988b, 1988c], Kemblowski [1988], White [1988], Molz and Güven [1988], Naff et al [1988, 1989], Dagan [1989], Zhang and Neuman [1990], Rajaram and Gelhar [1991], Ritzi and Allen‐King [2007], Woodbury and Sudicky [1992], and others.…”
Section: Introductionmentioning
confidence: 99%